JARIMAH KORUPSI SEBAGAI KEJAHATAN LUAR BIASA - Syarbaini, Ahmad (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2025)
Corruption comes from the Latin words corruptio and corruptus which means to bribe and corrumpere means to destroy. Corruption is included in the jarîmah, corruption in Indonesian law is: